Allied health in residential aged care: Using routinely collected data to improve funding opportunities. (7th September 2022) - Meulenbroeks, Isabelle; Seaman, Karla; Raban, Magdalena Z.; Westbrook, Johanna
Abstract: Consumers and providers have long been advocating for increased access to and delivery of allied health services in Australian residential aged care (RAC). There is significant evidence that allied health interventions are effective; however, there is limited evidence on the benefit of routine day‐to‐day allied health service delivery in RAC. This information is critical to effectively inform funders and policy advisors of the necessity of allied health in RAC. To improve arguments for future funding opportunities, providers, facilities and consumers need to partner together to use routinely collected, yet disparate, data, in electronic health and billing records, to improve data collection practices and evidence generation on allied health in aged care.